2013
DOI: 10.1002/aic.14127
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic CO2 fixation by the acetogenic bacterium Moorella thermoacetica

Abstract: Anaerobic bacteria such as Moorella thermoacetica have the capacity of fixing carbon dioxide with carbon monoxide and hydrogen for the production of ethanol, acetic acid, and other useful chemicals. In this study, we evaluated the fixation of CO2 for the production of acetic acid, as a product in its own right but also as precursor for lipid synthesis by oleaginous organisms. We achieved maximum cell optical density of 11.3, acetic acid titer of 31 g/L, and productivity of 0.55 g/L‐h at CO mass‐transfer rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…Although syngas has historically been used for gas engines and the production of bulk chemicals, such as methanol, acetate, and carbohydrate, by chemical processes, acetogens have recently received greater attention as hosts for producing biofuels and bulk chemicals from syngas (1). Acetogens can grow by using H 2 and CO as electron donors and CO 2 as a carbon source.…”
mentioning
confidence: 99%
“…Although syngas has historically been used for gas engines and the production of bulk chemicals, such as methanol, acetate, and carbohydrate, by chemical processes, acetogens have recently received greater attention as hosts for producing biofuels and bulk chemicals from syngas (1). Acetogens can grow by using H 2 and CO as electron donors and CO 2 as a carbon source.…”
mentioning
confidence: 99%
“…2, which presents time courses for growth and acetic acid titer in an anaerobic bubble column run independently. Our prior work provided the basis for flow rates relevant to this study (7). Fermentation was carried out at a flow rate of 1,000 standard cubic centimeters per minute (sccm), using either CO or H 2 as reducing gas at a composition of 7/3 CO/CO 2 or 7/3 H 2 /CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We have shown previously that acetate in excess of 30 g/L can be produced from mixtures of CO 2 and CO/H 2 , using an evolved strain of the acetogen Moorella thermoacetica, with a substantial productivity of 0.55 g·L −1 ·h −1 and yield of 92% (7). We also have demonstrated that the engineering of the oleaginous yeast Yarrowia lipolytica can yield biocatalysts that can produce lipids from glucose at high yields and productivities (2,5).…”
mentioning
confidence: 87%
“…Recently, Moorella thermoacetica, a thermophilic acetogenic bacterium which produces acetic acid as the only end product of the WL pathway, was used in a bubble column reactor for conversion of syngas to acetic acid with improved productivity [76]. Fermentation of CO by Clostridium carboxidivorans has also been performed, which showed the formation of acetic acid, butyric acid, and ethanol when pH was not regulated, whereas with pH regulation ethanol and butanol were formed both from CO fermentation and from the bioconversion of acetic-and butyric acids [77].…”
Section: Production Of Chemicals and Fuels From Carbon Dioxidementioning
confidence: 99%